TEACHER ASSESSMENT LITERACY: INDONESIAN EFL SECONDARY TEACHERS' SELF-PERCEIVED ON CLASSROOM-BASED ASSESSMENT PRACTICE - Dewi Aria; Didi Sukyadi; Eri Kurniawan (University of Kuningan, 2021)
Assessing students' performance is an essential part of a teacher's job. Hence, they are believed to be familiar with various kinds of assessments, especially classroom-based assessments (henceforth CBA). Language teaching and assessment are two interrelated that affect each other to a great extent. Undoubtedly, language assessment becomes a more complicated activity in the field of language teaching. The major objective of this study was to describe how EFL secondary teachers’ self-perceived on the basic principles of assessment and their own practice in CBA. This study was conducted in the form of a descriptive survey research. Shim's (2009) survey instrument was adapted to collect data and gathered using an online survey. 48 respondents willingly fulfilled the online survey containing 80 statements concerning classroom assessment procedures. The data obtained were analyzed using descriptive statistics. The findings of the current study revealed that teachers seemed to practice assessment for learning (henceforth AfL), in which most teachers conducted assessments to support students’ learning and used the results as feedback to improve and revise their teaching. The teachers in this study appeared to be literate and excellent in understanding the concept and using it in practice. However, a question remains as to whether their classroom practice was excellent. Since most studies have largely reported results on teacher's assessment literacy (henceforth TAL), future programs and research should be directed toward classroom-based research on how the CBAL can improve students' learning and improve the quality of teacher instructions. The implications of the result are expected to provide a clear understanding and theoretical foundations of CBAL.